CorrCompilations : corrosion control by organic coatings - Pogue, Robert (NACE International, 2016)
The papers included in this compilation were selected from those submitted to the NACE Corrosion Conference and Expo from 2010 to 2014 and represent several different sectors including infrastructure, power generation, utilities, transportation, and manufacturing, and were written by authors from around the globe. This collection is organized in three sections: "Coatings and Coating Selection," "Monitoring and Testing," and "Surface Preparation." The sections are meant to aid the reader with specifying, monitoring, and maintaining organic coatings for corrosion protection.